The racecar alphabet - Floca, Brian (New York : Atheneum Books for Young Readers, 2003)
An exciting day at the races highlights the letters of the alphabet as a variety of automobiles burn fuel speeding through the curves of the track.
"A Richard Jackson Book".
Keywords: Automobile racing -- Fiction; Automobiles, Racing -- Fiction; Alphabet